Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the problems [tex]\(27^2-26^2\)[/tex] and [tex]\(118^2-117^2\)[/tex] without actually calculating the squares, we can use the difference of squares formula. The difference of squares formula states that:
[tex]\[ a^2 - b^2 = (a - b)(a + b) \][/tex]
### Part (i) [tex]\(27^2 - 26^2\)[/tex]
Let's denote [tex]\(a = 27\)[/tex] and [tex]\(b = 26\)[/tex].
Using the formula:
[tex]\[ 27^2 - 26^2 = (27 - 26)(27 + 26) \][/tex]
Now, we calculate the values inside the parentheses:
[tex]\[ 27 - 26 = 1 \][/tex]
[tex]\[ 27 + 26 = 53 \][/tex]
Therefore:
[tex]\[ 27^2 - 26^2 = 1 \times 53 = 53 \][/tex]
So, the value of [tex]\(27^2 - 26^2\)[/tex] is [tex]\(53\)[/tex].
### Part (ii) [tex]\(118^2 - 117^2\)[/tex]
Let's denote [tex]\(a = 118\)[/tex] and [tex]\(b = 117\)[/tex].
Using the formula:
[tex]\[ 118^2 - 117^2 = (118 - 117)(118 + 117) \][/tex]
Now, we calculate the values inside the parentheses:
[tex]\[ 118 - 117 = 1 \][/tex]
[tex]\[ 118 + 117 = 235 \][/tex]
Therefore:
[tex]\[ 118^2 - 117^2 = 1 \times 235 = 235 \][/tex]
So, the value of [tex]\(118^2 - 117^2\)[/tex] is [tex]\(235\)[/tex].
In summary:
(i) [tex]\(27^2 - 26^2 = 53\)[/tex]
(ii) [tex]\(118^2 - 117^2 = 235\)[/tex]
[tex]\[ a^2 - b^2 = (a - b)(a + b) \][/tex]
### Part (i) [tex]\(27^2 - 26^2\)[/tex]
Let's denote [tex]\(a = 27\)[/tex] and [tex]\(b = 26\)[/tex].
Using the formula:
[tex]\[ 27^2 - 26^2 = (27 - 26)(27 + 26) \][/tex]
Now, we calculate the values inside the parentheses:
[tex]\[ 27 - 26 = 1 \][/tex]
[tex]\[ 27 + 26 = 53 \][/tex]
Therefore:
[tex]\[ 27^2 - 26^2 = 1 \times 53 = 53 \][/tex]
So, the value of [tex]\(27^2 - 26^2\)[/tex] is [tex]\(53\)[/tex].
### Part (ii) [tex]\(118^2 - 117^2\)[/tex]
Let's denote [tex]\(a = 118\)[/tex] and [tex]\(b = 117\)[/tex].
Using the formula:
[tex]\[ 118^2 - 117^2 = (118 - 117)(118 + 117) \][/tex]
Now, we calculate the values inside the parentheses:
[tex]\[ 118 - 117 = 1 \][/tex]
[tex]\[ 118 + 117 = 235 \][/tex]
Therefore:
[tex]\[ 118^2 - 117^2 = 1 \times 235 = 235 \][/tex]
So, the value of [tex]\(118^2 - 117^2\)[/tex] is [tex]\(235\)[/tex].
In summary:
(i) [tex]\(27^2 - 26^2 = 53\)[/tex]
(ii) [tex]\(118^2 - 117^2 = 235\)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.